UNCTAD conflict and compromise : the Third World's quest for an equitable world economic order through the United Nations - Gosovic, Branislav; United Nations Conference on Trade and Development (Leiden, A. W. Sijthoff international publishing company, 1972)
This book provides the origins, structure, and policies of the United Nations Conference on Trade and Development (UNCTAD). The book had its origins in the author's doctoral dissertation, subsequently summarized in a 1968 issue of International Conciliation. The book Begins with a brief historical survey the author first directs his attention to the 1964 Geneva Conference where the organization was created and its structure defined. Major areas of concern were delegated to standing committees, the functions and activities of which are discussed at length.
Abridged and updated version of the author's thesis, University of California, Berkeley.
Includes bibliographical references : p. 335-339.
lje 19/09/2018
Loans
Keywords: Economic assistance; Economic Development; United Nations Conference on Trade and Development; International Trade